Promoting self-management, health literacy and social capital to reduce health inequalities in older adults living in urban disadvantaged areas: protocol of the randomised controlled trial AEQUALIS - Laura Coll-Planas; Sergi Blancafort; Xavier Rojano; Marta Roqué; Rosa Monteserín (BMC, 2018)
Abstract Background Older people living in socio-economic deprived urban areas especially suffer the effects of health inequalities but have been insufficiently targeted. Strategies promoted by local primary health care agents might influence health and social behaviours as intermediate social determinants that are modifiable and thus can potentially mitigate health inequalities. Therefore, we aim to develop and assess the effectiveness of a complex intervention based on a community programme that promotes self-management, health literacy and social capital targeting older people from urban socioeconomically disadvantaged areas in order to improve their self-perceived health as an indicator of health inequality reduction. Methods/design Design: A pragmatic multicentre, parallel, randomised controlled trial will be implemented in 16 primary health care centres from six urban areas in neighbourhoods with low-socioeconomic level. Target: community-dwelling aged 60 years or above who perceive their health as fair or poor. The programme is called "Sentir-nos Bé" ("Feeling well") and comprises 12 two-hour sessions held once a week in groups of 12-15 people. Group dynamics are designed to promote mutual support, social participation and new knowledge on health literacy and self-management, resulting in meaningful changes in their daily life that positively affect their health and wellbeing. A sample size of 390 participants, randomised to the intervention or the control group, will be needed to detect a clinically relevant benefit in the primary outcome self-perceived health after 3-month intervention. A follow-up will be conducted at 9 months post-intervention. Participants in the control group will receive usual care and remain in a waiting-list to join the programme once the trial ends. A process evaluation will provide greater confidence in the conclusions about the effectiveness of the intervention. Ethics approval: Clinical Investigation Ethics Committee of the IDIAP Jordi Gol (P15/031). Dissemination: Findings will be disseminated through conference presentations and open-access journals. Discussion The project will promote the implementation of evidence-based intervention procedures in future health policy strategies targeting older people while considering the social aspects of inequality. Trial registration NCT02733523. Retrospectively registered. Date of registration: April 11, 2016.